PENGARUH CORPORATE GOVERNANCE STRUCTURE DAN KONSENTRASI KEPEMILIKAN PADA PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT - Agista, Gissel Glenda; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
The purpose is  to provide empirical evidence of corporate governance structure and ownership concentration influence to Enterprise Risk Management (ERM) disclosure at the Institute of Non-Bank Financial Services (LJKNB). Disclosure is important as a manifestation of transparency principle. Disclosure items used in this study was 25 items from ISO 31000 ERM to measure  disclosure index. Samples are LJKNB which consists of insurance, reinsurance, finance, and securities companies that listed in Indonesia Stock Exchange in 2014-2015. Samples were determined based on non-probability sampling method with purposive sampling technique and obtained 36 companies with 72 data observed. Hypothesis testing is performed with multiple linear regression. The results showed independent commissioner that measured by the proportion of commissioners did not affect on broad disclosure of ERM in LJKNB, while the Risk Management Committee (RMC), Chief Risk Officer (CRO), and ownership concentration had partial positive effect on the broad disclosure of ERM in LJKNB.
Keywords: ERM disclosure, corporate governance structure, ownership concentration